1996
DOI: 10.1016/s1074-7613(00)80411-2
|View full text |Cite
|
Sign up to set email alerts
|

A Pathogenetic Role for TNFα in the Syndrome of Cachexia, Arthritis, and Autoimmunity Resulting from Tristetraprolin (TTP) Deficiency

Abstract: Tristetraprolin (TTP) is a widely expressed potential transcription factor that contains two unusual CCCH zinc fingers and is encoded by the immediate-early response gene, Zfp-36. Mice made deficient in TTP by gene targeting appeared normal at birth, but soon manifested marked medullary and extramedullary myeloid hyperplasia associated with cachexia, erosive arthritis, dermatitis, conjunctivitis, glomerular mesangial thickening, and high titers of anti-DNA and antinuclear antibodies. Myeloid progenitors from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

41
847
2
5

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 723 publications
(895 citation statements)
references
References 18 publications
41
847
2
5
Order By: Relevance
“…In support of such a homeostatic mechanism, we have additionally observed that physiological membrane TNF expression is maintained also in cases where soluble TNF production is up-regulated such as in the case of the TTP-deficient model of TNF overexpression (Fig. 6) [45]. A relevant question that remains to be addressed is whether the TNF D1-12 mutant binds with the same affinity as the WT transmembrane TNF to TNFR1 and TNFR2.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…In support of such a homeostatic mechanism, we have additionally observed that physiological membrane TNF expression is maintained also in cases where soluble TNF production is up-regulated such as in the case of the TTP-deficient model of TNF overexpression (Fig. 6) [45]. A relevant question that remains to be addressed is whether the TNF D1-12 mutant binds with the same affinity as the WT transmembrane TNF to TNFR1 and TNFR2.…”
Section: Discussionmentioning
confidence: 60%
“…Such a protein is tristetraprolin (TTP), which binds to TNF3 0 ARE in an inducible fashion and promotes the rapid degradation of TNF mRNA. Mice with targeted deletions of this molecule express high levels of TNF mRNA and develop a TNFdependant-arthritic phenotype [45][46][47]. We hypothesized that the increased levels of endogenous TNF mRNA resulting from the absence of TTP would allow us to directly address the efficacy of tmTNF to induce the arthritic phenotype.…”
mentioning
confidence: 99%
“…The activation of p38 results in the phosphorylation of several intracellular substrates, including MapKapK-2 kinase and the activating transcription factor 2 (Waskiewicz and Cooper, 1995;Obata et al, 2000). As previously described, TTP promotes TNFa mRNA instability in mouse macrophages through direct interactions with its ARE (Taylor et al, 1996a;Carballo et al, 1997Carballo et al, , 1998Carballo et al, , 2000. It has recently been shown that TTP activation requires phosphorylation by p38 (Zhu et al, 2001).…”
Section: Regulation Of Are-binding Proteinsmentioning
confidence: 82%
“…TTP binds to 14-3-3 proteins, the binding being largely dependent upon a specific site in the TTP C terminus, and the interaction between TTP and 14-3-3 proteins is biologically significant in determining cytoplasmic localization. Mice deficient in TTP develop a complex phenotype consisting of cachexia, dermatitis, conjunctivitis, destructive arthritis, myeloid hyperplasia, and autoimmunity (Taylor et al, 1996a). Virtually, all aspects of this phenotype can be prevented by the repeated injection of antibodies to TNFa, implicating an effective excess of circulating TNFa in the pathogenesis of this condition.…”
Section: Tristetraprolinmentioning
confidence: 99%
“…Another study demonstrates that MCPIP1 knockout mice shows severe anemia and immune disorder (Matsushita et al, 2009). This phenomenon has also been found in other CCCH zinc-finger-containing proteins such as tristetraprolin (TTP) and Roquin (Taylor et al, 1996;Vinuesa et al, 2005;Yu et al, 2007). Recently, numerous studies have focused on the RNase activity of MCPIP1 targeting on the mRNAs of IL-6, IL-1β (Matsushita et al, 2009;Mizgalska et al, 2009), and pre-microRNAs (Suzuki et al, 2011).…”
Section: Introductionmentioning
confidence: 75%